Imposition of Criminal Sanctions on Suspects Who Commit Criminal Acts in Detention Centers (Review of Criminal Law and Islamic Criminal Law) - Ucha Saleha Nasution; Mar`ie Mahfudz Harahap2 (Warmadewa Press, 2024)
This study discusses the sanctions given to a person who commits more than one criminal act at different times before the judge's decision (during the detention period). This study aims to find out the regulation of criminal merger in positive criminal law, to find out the merger of crimes in decision number 2739/Pid.B/2020/PN Lbp and in the verdict number 2360/Pid.B/2021/PN Lbp and know the incorporation of crime in Islamic criminal law. This type of research is normative juridical, with a comparative approach method. The data source uses secondary data in the form of books. Data collection through journals and other legal sources. The data analysis technique used is descriptive-qualitative analysis. Crime is increasing, and this study shows that a person who is still in the legal process can still commit a criminal act, in this case it is called a combination of criminal acts. Based on the results of research and discussion, it is known that criminal mergers are divided into three types, namely: Concursus Idealis, Vorgezette Handeling, dan Concursus Realis. The penal system in the Criminal Code is divided into three, namely absorbs, accumulation, weighted absorbs and limited accumulation. In Islamic criminal law, merger is known as ta’addudul uqbad (Multiple punishments) dan al-ijtimaul ‘uqubah (The accumulation of several punishments). Getting to know three theories, namely the theory of Mutual Penetration/Entry (At-Tadkhul), Absorption Theory (al Jabbu), and mixed theory.